Development of Formative Assessment Based on Educational Games Integrated with QR Code on Popular Scientific Article Material - Dewi Rahayu; Kembong Daeng; Hajrah Hajrah (SAWERIGADING, 2025)
The Indonesian language subject presents various types of text-based materials. One of the less popular topics among students is popular scientific articles. This material is taught in Grade VIII of junior high schools across Indonesia. A key factor contributing to students' lack of interest in this topic is the continued use of conventional assessment methods by teachers, which makes the evaluation process less engaging. To address this issue, a more creative approach such as implementing educational game-based formative assessment can help increase students' interest and understanding of popular scientific articles. This study aims to describe the feasibility, practicality, and effectiveness of a QR code integrated educational game-based formative assessment on the topic of popular scientific articles. This research and development was conducted following the steps developed by Thiagarajan through the 4-D model, which includes four stages: Define, Design, Develop, and Disseminate. The results of the study show that the feasibility validation of the QR code-integrated educational game-based assessment reached 87%, indicating a very feasible level. In terms of practicality, it achieved a score of 92%, categorized as very practical, and for effectiveness, the score was 76.25%, falling into the effective category. AbstrakMata pelajaran Bahasa Indonesia menyajikan berbagai jenis materi dalam berbasis teks. Salah satu materi yang kurang diminati oleh siswa yaitu materi artikel ilmiah populer. Materi ini diajarkan di kelas VIII jenjang SMP di seluruh Indonesia. Salah satu faktor utama yang menyebabkan rendahnya minat siswa terhadap materi ini adalah guru masih menggunakan metode penilaian konvensional, yang membuat proses evaluasi menjadi kurang menarik. Untuk mengatasi masalah ini, pendekatan yang lebih kreatif seperti penerapan asesmen formatif berbasis game edukatif dapat membantu meningkatkan minat dan pemahaman siswa terhadap materi artikel ilmiah populer. Penelitian ini bertujuan untuk mendeskripsikan kelayakan, kepraktisan, dan keefektifan asesmen formatif berbasis game edukatif yang terintegrasi qr code pada materi artikel ilmiah populer. Penelitian dan pengembangan ini dilakukan dengan mengikuti tahapan model 4-D yang dikembangkan oleh Thiagarajan, yang meliputi empat tahap: Define (pendefinisian), Design (perancangan), Develop (pengembangan), dan Disseminate (penyebarluasan). Hasil penelitian menunjukkan bahwa validasi kelayakan asesmen berbasis game edukatif yang terintegrasi qr code mencapai 87%, yang menunjukkan kategori sangat layak. Dari segi kepraktisan, diperoleh persentase sebesar 92% yang termasuk dalam kategori sangat praktis, dan dari segi keefektifan, persentase yang dicapai adalah 76,25%, yang tergolong dalam kategori efektif.